1982
DOI: 10.1002/art.1780250307
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factor inhibition of in vitro binding of IgG complexes in the human glomerulus

Abstract: We studied the effects of rheumatoid factor (RF) on binding of immune complexes to activated C3 (C3b) receptors in vitro. IgM fraction of serum containing RF activity (IgM‐RF), IgM isolated from pooled normal human serum and having no RF activity (IgM‐control), bovine serum albumin, and Veronal buffered saline solutions were used in a C3b assay system consisting of aggregated human IgG (AggHuIgG) coupled to sheep erythrocytes (SRBC) with guinea pig and normal human serum complement. The number of glomerular bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In another study, it was shown that IgM-RF could block attachment of C3b, which is capable of reacting with glomeruli receptors, indicating that IgM-RF can inhibit binding of immune complexes to human glomer- uli (29). This in vitro phenomenon may represent a possible protective mechanism of RF in vivo in immune complex diseases.…”
Section: Protective Antibodies In Autoimmune Diseasesmentioning
confidence: 95%
“…In another study, it was shown that IgM-RF could block attachment of C3b, which is capable of reacting with glomeruli receptors, indicating that IgM-RF can inhibit binding of immune complexes to human glomer- uli (29). This in vitro phenomenon may represent a possible protective mechanism of RF in vivo in immune complex diseases.…”
Section: Protective Antibodies In Autoimmune Diseasesmentioning
confidence: 95%
“…It has also been shown that RF blocks the attachment of C3 to aggregated IgG, not allowing its reaction with C3b receptors of glomeruli and thus shielding them from deposition of pathogenic immune complexes. 22…”
Section: Discussionmentioning
confidence: 99%
“…Another may be to reduce the binding of the first component of complement to IgG. Since RF may reduce the total complement binding to immune complexes, it may reduce the attachment of the complexes to C3 receptors in the renal glomerulus, thus preventing glomerulone phritis [6], Of main general biological signifi cance is the possibility that RF may clear the periphery and tissues of idiotype-anti-idiotype immune complexes [39]. The continued prevalence of RF in various autoimmune diseases and in many elderly individuals may simply imply changes in the homeostatic feedback mechanisms associated with or fol lowing the development of immunodefi ciency states that may accompany these con ditions [31],…”
Section: Discussionmentioning
confidence: 99%